2020
DOI: 10.3389/fpubh.2020.581373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Workaholism Among Egyptian Healthcare Workers With Assessment of Its Relation to Quality of Life, Mental Health and Burnout

Abstract: Introduction: Work is a social double edged weapon activity that may have positive and negative effects on individual's quality of life and health.Objectives: To estimate workaholism prevalence and to determine its effects on quality of life, mental health, and burnout among healthcare workers (HCWs).Methods: Using a cross-sectional study, 1,080 Egyptian participants distributed as HCWs and non-HCWs were recruited. The study included 4 questionnaires to assess workaholism, quality of life (QoL), Psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 48 publications
(56 reference statements)
5
26
0
Order By: Relevance
“…Burnout syndrome has been associated with mental health problems, including depression, anxiety, and stress [40], constructs that may be similar on a biological level [41]. Kasemy et al [70] found that emotional exhaustion is associated with some proinflammatory markers, including interleukin 6, TNFα, and coenzyme Q10, and inflammation is a key factor in the development of some mental health problems [71], including depression [72] and anxiety [73]. Our findings are consistent with the importance of learning burnout on psychological distress and suggest that learning burnout plays a crucial role in the association of physical exercise with psychological distress in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout syndrome has been associated with mental health problems, including depression, anxiety, and stress [40], constructs that may be similar on a biological level [41]. Kasemy et al [70] found that emotional exhaustion is associated with some proinflammatory markers, including interleukin 6, TNFα, and coenzyme Q10, and inflammation is a key factor in the development of some mental health problems [71], including depression [72] and anxiety [73]. Our findings are consistent with the importance of learning burnout on psychological distress and suggest that learning burnout plays a crucial role in the association of physical exercise with psychological distress in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the diurnal difference in cortisol levels, blood samples were drawn at a specific time of day (6–10 am). We measured CoQ10 using an ELISA (Sino Gene Clon Biotech Co., Ltd) with cut-off ranges of 1.56 ng/ml, 1.56 ng/ml, and 50 ng/ml ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, regarding individual characteristics related to workaholism, self-esteem, recognition of strengths, resilience, work meaningfulness, psychological safety, and the Big Five have been discussed in relevant literature (e.g., Barrick and Mount, 1991 ; Burke et al, 2006 ; Graves et al, 2012 ; Clark et al, 2016 ; Gillet et al, 2017 ; Choi et al, 2020 ; Kasemy et al, 2020 ; Kun et al, 2020 ). As their corresponding measurements were available in the dataset we used, we considered the possibility of including them as control variable in our analyses.…”
Section: Methodsmentioning
confidence: 99%